HISTORY OF COOPERATION BETWEEN UZBEKISTAN AND SOUTH KOREA (ON THE EXAMPLE OF LABOR MIGRATION) - Rahımberdıyev Sardorbek Bekmurod O‘G’li; Jaxongır Rustamalıyev Fakhrıddın O‘G’li; No‘Monov Kamronbek Kozımjon O‘G’li (Western European Studies, 2025)
This article analyzes the political, economic and cultural relations between South Korea and Uzbekistan. In particular, it examines the migration processes between the two countries, the flow of labor migration, its causes and consequences, and the impact of these processes on bilateral relations. The article uses an analytical approach based on official cooperation agreements, the role of the Korean diaspora, and the conditions created for labor migrants. During the study, statistical data, intergovernmental agreements, and social processes are analyzed and recommendations are made to improve migration policy. This article serves to highlight new stages and prospects for cooperation between the two countries.
Keywords: Republic of Korea; migration; demographics